Investigating the Relationship Between Central Bank Transparency and Stock Market Volatility in a Nonparametric Framework - Stephanos Papadamou; Moise Sidiropoulos; Nickolaos Tzeremes (Credit and Capital Markets – Kredit und Kapital, 2017)
This study investigates whether any non-linear relationship exists between central bank transparency and stock market variability in a non-parametric framework for a large number of countries. Our findings imply that a high level of transparency can significantly reduce historical as well as conditional stock market volatility in a non-linear manner. The negative effect of transparency on stock volatility is clearer when we move from low levels towards higher levels of transparency; this effect diminishes as long as we move to higher levels of transparency. This analysis implies that monetary authorities can contribute to equity market stability by adopting more transparent monetary policies in the early stages. – – Untersuchung des Zusammenhangs zwischen der Transparenz von Zentralbanken und der Volatilität von Aktienmärkten in einem parameterfreien Rahmen Diese Studie untersucht, ob ein nicht-linearer Zusammenhang zwischen der Transparenz von Zentralbanken und der Varianz von Aktienmärkten in einem parameterfreien Rahmen für eine große Anzahl an Ländern existiert. Die Ergebnisse lassen darauf schließen, dass ein hoher Grad an Transparenz sowohl die historische als auch die bedingte Volatilität von Aktienmärkten auf nicht-lineare Weise signifikant reduzieren kann. Der negative Effekt von Transparenz auf die Volatilität von Aktien wird umso deutlicher, je mehr man sich von niedrigen Niveaus in Richtung höherer Niveaus an Transparenz bewegt. Die Untersuchung deutet darauf hin, dass die Notenbanken zur Aktienmarktstabilität beitragen können, wenn sie frühzeitig eine transparentere Geldpolitik anwenden.
Keywords: E52; E5; C14; 330; Local linear estimators; nonparametric regression; central bank; transparency